WAWASAN KERUKUNAN BERAGAMA DI INDONESIA - Muhammad Fakhri (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
Indonesia with a population of more than 200 million consisting of thousands of islands with different ethnic background, religion, culture, customs and so forth. Differences are bound by the motto Bhineka Tunggal Ika, which means a variety in one bond. Formerfy the motto is quite powerful and can be relied upon by the whole society. Indonesia is known as a safe country, peaceful harmonious and peaceful In the era of democracy and how trancparency today Indonesai a build religious harmony insight into the foundations of upholding the integrity of the nation? Menanamkna Among them are the principles of tolerance among religious communities